Use of soil test kits in assessing soil fertility of castor growing soils of semi-arid tropics: USE OF SOIL TEST KITS IN ASSESSING FERTILITY OF CASTOR GROWING SOILS OF SEMI-ARID TROPICS - I Y L N MURTHY; CH V HARIPRIYA; M PADMAIAH (Journal of Oilseeds Research, 2015)
Resource poor farmers use semi-arid tropic soils of southern India for castor cultivation. These soils are well known for their low soil fertility thus resulting in poor castor seed yield. Conventional soil tests of laboratory will take more time. Based on these, fertiliser recommendations to the farmers is seldom delivered in time. Soil test kits (STKs) developed by Acharya N G Ranga Agricultural University, Hyderabad and Coromandal Fertilisers Ltd., Secunderabad is quiet handy in determining the physico-chemical properties on the spot and advice fertiliser recommendations to the farmers. In the present study, results obtained by using these STKs and conventional laboratory testswere compared. The parameters viz., pH, organic carbon, available nitrogen, phosphorus, potassium, sulphur and micronutrients (zinc, boron and iron) were in close agreement with that of laboratory tests. Thus, for a quick diagnosis of soil fertility status, STKs are highly useful and accordingly fertiliser recommendations can be given to farmers.